2016
DOI: 10.1016/j.toxrep.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals contamination and human health risk in shrimp collected from different farms and rivers at Khulna-Satkhira region, Bangladesh

Abstract: This study is aimed to assess the heavy metals contamination and health risk in Shrimp (Macrobrachium rosenbergii and Penaeus monodon) collected from Khulna-Satkhira region in Bangladesh. The results showed that the Pb concentrations (0.52–1.16 mg/kg) in all shrimp samples of farms were higher than the recommended limit. The Cd levels (0.05–0.13 mg/kg) in all samples and Cr levels in all farms except tissue content at Satkhira farm were higher than the permissible limits. The individual concentration of Pb, Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 12 publications
6
58
3
2
Order By: Relevance
“…The slight increase in Zn BAF in fish is also consistent with the biomagnifying potential of Zn in marine fish food chains (Wang, 2002). Conversely, the higher Cd bioaccumulation we observed in zooplankton fractions (mainly composed of copepods and crustacean larvae) versus fish may be linked to efficient copepod Cd assimilation (Twining and Fisher, 2004) and the ability of crustaceans to accumulate high quantities of Cd in their exoskeleton (Sarkar et al, 2016).…”
Section: Patterns Of Metal Bioaccumulation In the Study Food Web (Bafs)supporting
confidence: 79%
“…The slight increase in Zn BAF in fish is also consistent with the biomagnifying potential of Zn in marine fish food chains (Wang, 2002). Conversely, the higher Cd bioaccumulation we observed in zooplankton fractions (mainly composed of copepods and crustacean larvae) versus fish may be linked to efficient copepod Cd assimilation (Twining and Fisher, 2004) and the ability of crustaceans to accumulate high quantities of Cd in their exoskeleton (Sarkar et al, 2016).…”
Section: Patterns Of Metal Bioaccumulation In the Study Food Web (Bafs)supporting
confidence: 79%
“…So the sediments could be the major sources of Pb contamination and the bottom feeders may directly affects with this deposited element in consequence to their feeding habitat (Garcia et al, 2010). Zn is the essential element for both human and aquatic organisms and they showed productive activity against Cd and Pb toxicity in biological organisms (Sarkar et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Another research showed that there were 29 fish species in South China Sea, they are ; 51-115.81 ng/g (Cd), 0.54-27.31 ng/g (Pb), 0.02-1.26 μg/g (Cr), 8.32-57.48 ng/g (Ni), 0.12-1.13 μg/g (Cu), 2.34-6.88 μg/g (Zn), 2.51-22.99 μg/g (Fe), and 0.04-0.81 μg/g (Mn) [7]. Moreover, heavy metals are also identified in river,Pb, Cr and Zn consentration in many fish samples exceed consumption limits [19], and it is contaminated by heavy metals in shrimp (Macrobrachiumrosenbergii and Penaeusmonodon) that are collected from Khulna-Satkhira area in Bangladesh with concentration; Pbthat is (0.52-1.16 mg/kg) and Cd that is (0.05-0.13 mg/kg) [20].…”
Section: Discussionmentioning
confidence: 99%